Sustainable utilization and valorization of potato waste: state of the art, challenges, and perspectives - Khanal, Sonali; Karimi, Keikhosro; Majumdar, Sneha; Kumar, Vinod; Verma, Rachna; Bhatia, Shashi Kant; Kuca, Kamil; Esteban, Jesús; Kumar, Dinesh (Springer, 2023)
Potatoes (Solanum tuberosum L.) are starchy tuberous crops that represent the world’s fourth most important crop. According to the “Food and Agricultural Organisation of the United Nations,” 376 million metric tonnes of potatoes were produced globally in 2021. It is anticipated that around 8000 kilotons of potato peel waste might be generated in 2030, with related greenhouse gas emissions of 5 million tonnes of CO2 equivalent. Waste generated throughout the food supply chain, from potato farms to forks, contributes considerably to global warming. Apart from animal feed, technical processes in the potato processing industry generate waste organic residues with high amounts of bioactive compounds and carbohydrates, and thus extraction and bioconversion processes can produce high-value products. These include the isolation of functional ingredients for the formulation of nutraceuticals and pharma products, bioenergy-related products, enzymes, and fertilizers for the market, hence contributing to a more responsible production and consumption and, overall, circular economy. This review focuses on studies involving potato waste from industries such as pulp, processed water, peels, and mash showing the great prospects of the by-products from this crop for value-added supply chains and the reduction of undesired environmental effects. This work attempts to adhere upon several Sustainable Development Goals, specifically goals 7, 12, and 13, while also contributing to long-term growth targets and reducing negative environmental consequences produced by the food sector.
Keywords: Waste valorization; Potato peel waste; Biorefinery; Value-added products; Phenolic compounds; Potato varieties